PERSEPSI PEMERINTAH DAN MASYARAKAT DALAM PELESTARIAN CAGAR BUDAYA: STUDI KASUS KAWASAN CAGAR BUDAYA PUSAT PEMERINTAHAN KESULTANAN SIAK SRI INDRAPURA - Ginanjar, Agi (UI Scholars Hub, 2024)
This article discusses the importance of government and community collaboration in the preservation and potential use of Siak Sri Indrapura Cultural Heritage Area. It is not easy to carry out preservation as mandated by the law, because in practice various problems may arise, especially those related to the area’s use. The purpose of this study is to integrate interpretations concerning the importance of government and community collaboration in the preservation of cultural heritage areas and those concerning their potential use by taking into account socio-cultural and economic values. This study was designed using a convergent qualitative and quantitative approach (convergent mixed methods approach) to collect data. Those data were then analyzed separately, and the results were then compared, resulting in whether findings in the form of mutual information become normalized or, conversely, do not normalize each other. This study identified the need for community participation in compiling significant values of the heritage and the similarity between government’s interpretation and public perception of socio-cultural and economic values.